2015
DOI: 10.1186/s12904-015-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for effective goals of care discussions and decision-making: perspectives from a multi-centre survey of Canadian hospital-based healthcare providers

Abstract: BackgroundCommunication gaps impact the quality of patient care. Previous research has focused on communication barriers rather than seeking solutions. Our aim was to identify strategies for effective communication and decision-making about goals of care for medical interventions in serious illness, from the perspectives of hospital-based healthcare providers.MethodsA cross-sectional survey composed of closed- and open-ended questions about goals of care communication and decision-making was administered to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…We and others have described how ACP can be a care team responsibility, where interprofessional team members contribute to different aspects of ACP. 1,3,7,20 Similar to how management of hypertension involves several disciplines to assess, diagnose, treat, and monitor blood pressure, our findings suggest opportunities to review ACP clinical workflows and identify appropriate responsibilities for each team member to optimize patient engagement in ACP.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We and others have described how ACP can be a care team responsibility, where interprofessional team members contribute to different aspects of ACP. 1,3,7,20 Similar to how management of hypertension involves several disciplines to assess, diagnose, treat, and monitor blood pressure, our findings suggest opportunities to review ACP clinical workflows and identify appropriate responsibilities for each team member to optimize patient engagement in ACP.…”
Section: Discussionmentioning
confidence: 81%
“…6 A recent study of Canadian inpatient physicians and nurses identified potential targets for improving clinical workflows related to communication and decision-making about goals of care, including patient/family factors, communication between health care providers and patients, interprofessional collaboration, education, and resources. 7 Taken together, these studies allude to widespread need for systematic clinical routines to facilitate ACP in clinical settings and that physicians may not be the most appropriate interprofessional team member to be responsible for all ACP-related activities given time constraints and workforce shortages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study described the patient and family perspective of confusion and disruption that can take place during goals of care discussions and highlighted the need for health care teams to communicate effectively with patients. Ordons et al (2015) conducted a thematic analysis of a survey composed of open and closed-ended questions administered to healthcare professionals in thirteen centers in Canada, to explore factors that impacted goals of care discussions. Major themes identified were 1) patient and family factors-advanced illness was a trigger to initiate goals of care (GOC) and identify decision makers 2) communication between health care provider and patient-identified timing, content, process and continuity of communication as mechanism to improve GOC discussions 3)…”
Section: Factors Impacting Goals Of Care Discussionmentioning
confidence: 99%
“…11,12,13 Investigations focused on interventions to improve goal elicitation and patient satisfaction regarding whiteboard usage and nurse-led initiatives provided the inspiration for this project. 18,19,20 Recording daily goals on a whiteboard facilitates a consistent plan of care, goal directed care, and provides health care providers with a daily list of patient goals to review.…”
Section: Review Of Literaturementioning
confidence: 99%